The generalised discrete algebraic Riccati equation arising in LQ optimal control problems: Part II - Ferrante, A.; Ntogramatzidis, Lorenzo (IEEE, 2012)
In this paper we develop an analytic approach to the solution of a very general class of discrete finite horizon optimal control problems. This method hinges on a new decomposition of the so-called extended symplectic pencil. Interestingly, the results established in this paper hold under assumptions that are weaker than the ones considered in the literature so far.